Formação de educadores musicais: em busca de uma formação humanizadora - Severino, Natália Búrigo (Universidade Federal de São Carlos, 2014)
This research is based on Paulo Freire, Carlos Rodrigues Brandão and Ernani Maria Fiori ideas about education for dialogue, respect and not oppression, known as humanizing education. According to that, authors as HJ Koellreutter, Carlos Kater, Maura Penna and Ilza Joly, help us to defend humanizing education within the field of Music Education. When advocating for humanizing musical education we must also defend the teaching fomation to work within this perspective. Thus, a qualitative research accompanied a group of undergraduate students in music education, which are working with music in public schools through a scholarship program named Institutional Scholarship Program for Teaching Initiation (PIBID). From the framework adopted, the observations made as a music mentor of these students, and the use of a daily field diary, we raised a list of skills and attitudes necessary for an educator seeking to act under the humanizing perspective. The researcher made interventions, and dynamic activities with these undergraduate students to instigate them, to question them, and propose a reflection on their own teaching practice. From these interventions, several pathways and its obstacles were pointed to a teaching formation that aims and cares about the human as a being. During these two years of research, a cyclic pattern was identified regards to how the licensees relates with their job in PIBID. This cycle was analysed from Michaël Huberman analysis about the teaching career cycle, which gave elements to comprehend the teaching experience and their formation. We noticed that to the student become a loving, respectful and dialogical musical educator, therefore humanizing, their formation must be founded in this same principles. This means that the training teacher, who accompainying the undergraduate from the beggining of their program must be loving, respectfull and dialogical. Hopefully, this research will contribute to the field of education and music education, presenting a new concept of music education and showing the necessity and importance of thinking, with commitment and respect, the teaching formation of musical educators to act in Brazilian schools.
Keywords: Educação musical; Formação inicial; Música na educação; Processo educativo; PIBID; Humanizing music education; Teaching education; Music in schools; Educative processes; CIENCIAS HUMANAS::EDUCACAO